2003
DOI: 10.1051/0004-6361:20030816
|View full text |Cite
|
Sign up to set email alerts
|

Dielectronic recombination data for dynamic finite-density plasmas

Abstract: Abstract.A programme is outlined for the assembly of a comprehensive dielectronic recombination database within the generalized collisional-radiative (GCR) framework. It is valid for modelling ions of elements in dynamic finite-density plasmas such as occur in transient astrophysical plasmas such as solar flares and in the divertors and high transport regions of magnetic fusion devices. The resolution and precision of the data are tuned to spectral analysis and so are sufficient for prediction of the dielectro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
282
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(288 citation statements)
references
References 46 publications
3
282
0
Order By: Relevance
“…Our ionization solver accounts for photoionization, collisional ionization, direct and dielectronic recombination, and charge transfer recombination. Photoionization cross-sections are taken from Verner et al (1996); collisional photoionization rates are from Voronov (1997); direct and dielectronic recombinations are from Badnell (2006) and Badnell et al (2003), respectively; and charge transfer recombination rates are from Kingdon & Ferland (1996). The local hydrogen ionization state is fixed to the nonequilibrium value stored in the simulation snapshot, and the electron abundance is taken as the value from the simulation owing to ionization of hydrogen and helium plus the small contribution from ionized metals.…”
Section: Generating Simulated Spectramentioning
confidence: 99%
“…Our ionization solver accounts for photoionization, collisional ionization, direct and dielectronic recombination, and charge transfer recombination. Photoionization cross-sections are taken from Verner et al (1996); collisional photoionization rates are from Voronov (1997); direct and dielectronic recombinations are from Badnell (2006) and Badnell et al (2003), respectively; and charge transfer recombination rates are from Kingdon & Ferland (1996). The local hydrogen ionization state is fixed to the nonequilibrium value stored in the simulation snapshot, and the electron abundance is taken as the value from the simulation owing to ionization of hydrogen and helium plus the small contribution from ionized metals.…”
Section: Generating Simulated Spectramentioning
confidence: 99%
“…3.2. We use the photoionization cross-sections in Verner et al (1993), charge exchange reaction rate coefficients from McElroy et al (2013), Lin et al (2005), and Kingdon & Ferland (1996), and electron recombination rate coefficients from Nahar & Pradhan (1997), Badnell et al (2003) and Badnell (2006). We show in Fig.…”
Section: X-ray Ionization Of Nitrogen and Oxygenmentioning
confidence: 99%
“…(4) and (5)] includes only the lower 19 terms or what is defined as the direct part. 20,21 To account for the higher Rydberg contributions or "cascades" into the lower term populations, we make use of the projection matrix that contains the equivalent of these contributions, and in this way build our generalized collisional radiative model by adding the N-term direct contribution C dir ij , with the higher Rydberg contributions or indirect contribution C indir ij . 20,21 Our comprehensive collisional radiative matrix is simply given by…”
Section: Equilibrium Collisional Radiative Modelmentioning
confidence: 99%
“…17 For comparison, we also generate a generalized CRM by means of the projection matrix from bundle-n onto a resolved nl low term solution. 3,20,21 This method helps us to include contributions from higher Rydberg states by condensing those high terms into the lower and limited N-term model we are using. Muñoz et al 22 have shown that there are significant differences when including the high Rydberg contributions into the helium model when applying the line ratio diagnostic for higher electron temperature-density regions, and which are well within the range of application of the hybrid solution.…”
Section: Introductionmentioning
confidence: 99%